Apoptotic vesicle-hybridized nanosponges enable dual-phase immunomodulation for targeted periodontitis therapy - Xiao-Ru Xu; Xin-Yan Luo; Lu-Fan Yang; Fei-Ran Wang; Jia-Wei Lu; Bai-Ting Luan; Yuan Yuan; Zi-Qi Zhang; Jin-Yu Liu; Yuan-Yuan Li; Yi-Han Liu; Yu Fu; et al. (Chemical Engineering Journal, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Chronic intermittent hypoxia modulates energy metabolic pathways and improves hypoxia tolerance capacity in golden pompano, Trachinotus blochii - Geng Hui Fang; Xiao Li Zhou; Chun Li Ran; Chun Xiu Jin; Shao Yang Bu; Yue Chen; Yong Gong; Zeng Tan Hu; Fei Biao Song; Jian Luo; Jun Long Sun (Science of The Total Environment, 2025)

Spatiotemporal distribution and impact factors of GNSS-PWV in China based on climate region - Fei Yang; Xu Gong; Zhicai Li; Yingying Wang; Shiji Song; Haoyu Wang; Ran Chen (Advances in Space Research, 2024)

Recent progress in γ-Fe2O3-based catalysts: An overview of the synthesis and applications in environmental remediation - Yuzhuo Zhou; Xin Yang; Chen Gong; Fei Zhu; Jian Wang; Yongfeng Qi; Kai Huang; Jiang Wu; Ran Chen; Yi Liu (Chemical Engineering Journal, 2023)

Spring photosynthetic phenology of Chinese vegetation in response to climate change and its impact on net primary productivity - Yingying Xue; Xiaoyong Bai; Cuiwei Zhao; Qiu Tan; Yangbing Li; Guangjie Luo; Luhua Wu; Fei Chen; Chaojun Li; Chen Ran; Sirui Zhang; Min Liu; et al. (Agricultural and Forest Meteorology, 2023)

Climate change has enhanced the positive contribution of rock weathering to the major ions in riverine transport - Suhua Gong; Xiaoyong Bai; Guangjie Luo; Chaojun Li; Luhua Wu; Fei Chen; Chen Ran; Huipeng Xi; Sirui Zhang (Global and Planetary Change, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Responses of carbon and water use efficiencies to climate and land use changes in China's karst areas - Biqin Xiao; Xiaoyong Bai; Cuiwei Zhao; Qiu Tan; Yangbing Li; Guangjie Luo; Luhua Wu; Fei Chen; Chaojun Li; Chen Ran; Xuling Luo; Huipeng Xi; et al. (Journal of Hydrology, 2023)

High‐resolution mapping of the global silicate weathering carbon sink and its long‐term changes - Chaojun Li; Xiaoyong Bai; Qiu Tan; Guangjie Luo; Luhua Wu; Fei Chen; Huipeng Xi; Xuling Luo; Chen Ran; Huan Chen; Sirui Zhang; Min Liu; et al. (Global Change Biology, 2022)
Climatic and non‐climatic factors affect the chemical weathering of silicate rocks, which in turn affects the CO 2 concentration in the atmosphere on a long‐term scale. However, the coupling effects of these factors prevent us from clearly understanding of the global weathering carbon sink of silicate rocks. Here, using the improved first‐order model with correlated factors and non‐parametric methods, we produced spatiotemporal data sets (0.25° × 0.25°) of the global silicate weathering carbon‐sink flux (SCSF α ) under different scenarios (SSPs) in present (1950–2014) and future (2015–2100) periods based on the Global River Chemistry Database and CMIP6 data sets. Then, we analyzed and identified the key regions in space where climatic and non‐climatic factors affect the SCSF α . We found that the total SCSF α was 155.80 ± 90 Tg C yr −1 in present period, which was expected to increase by 18.90 ± 11 Tg C yr −1 (12.13%) by the end of this century. Although the SCSF α in more than half of the world was showing an upward trend, about 43% of the regions were still showing a clear downward trend, especially under the SSP2‐4.5 scenario. Among the main factors related to this, the relative contribution rate of runoff to the global SCSF α was close to 1/3 (32.11%), and the main control regions of runoff and precipitation factors in space accounted for about 49% of the area. There was a significant negative partial correlation between leaf area index and silicate weathering carbon sink flux due to the difference between the vegetation types. We have emphasized quantitative analysis the sensitivity of SCSF α to critical factors on a spatial grid scale, which is valuable for understanding the role of silicate chemical weathering in the global carbon cycle.

Comparison of SPE, IFE, and FLC in Monitoring Patients with Multiple Myeloma After Autologous Stem Cell Transplantation - Wei Li; Jia-Zi Zhou; Hui-Rong Chang; Li-Jun Dai; Zi-Ling Zhu; Yu-Feng Feng; Fei-Ran Gong; De-Pei Wu (Cell Biochemistry and Biophysics, 2015)

True-amplitude wavefield separation using staggered-grid interpolation in the wavenumber domain - Qi-Zhen Du; Ming-Qiang Zhang; Xiao-Ran Chen; Xu-Fei Gong; Cheng-Feng Guo (Applied Geophysics, 2014)